Astragaloside IV improves lipid metabolism in obese mice by alleviation of leptin resistance and regulation of thermogenic network - Wu, Hui (Sci Rep, 2016)
Obesity is a worldwide threat to public health in modern society, which may result from leptin resistance and disorder of thermogenesis. The present study investigated whether astragaloside IV (ASI) could prevent obesity in high-fat diet (HFD)-fed and db/db mice. In HFD-fed mice, ASI prevented body weight gain, lowered serum triglyceride and total cholesterol levels, mitigated liver lipid accumulation, reduced fat tissues and decreased the enlargement of adipose cells. In metabolic chambers, ASI lessened appetite of the mice, decreased their respiratory exchange ratio and elevated VCO(2) and VO(2) without altering circadian motor activity. Moreover, ASI modulated thermogenesis associated gene expressions in liver and brawn fat tissues, as well as leptin resistance evidenced by altered expressions of leptin, leptin receptor (ObR) or appetite associated genes. In SH-SY5Y cells, ASI enhanced leptin signaling transduction. However, in db/db mice, ASI did not change body weight gain and appetite associated genes. But it decreased serum triglyceride and total cholesterol levels as well as liver triglyceride. Meanwhile, it significantly modulated gene expressions of PPARα, PGC1-α, UCP2, ACC, SCD1, LPL, AP2, CD36 and SREBP-1c. Collectively, our study suggested that ASI could efficiently improve lipid metabolism in obese mice probably through enhancing leptin sensitivity and modulating thermogenic network.